Acute Generalized Exanthematous Pustulosis Resembling Generalized Pustular Psoriasis In A Patient with Psoriasis History: A Diagnostic Challenge - Aziz, Yusuf Abdullah; Nurwina, Hasna Syifa; Nafasadila, Fatma; Pramuningtyas, Ratih; Prakoeswa, Flora Ramona Sigit (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Acute generalized exanthematous pustulosis (AGEP) and generalized pustular psoriasis (GPP) are two rare dermatologic conditions that have similar clinical presentations. This case report discusses the challenges in differentiating AGEP and GPP in a 27-year-old man with a history of psoriasis. The patient presented with complaints of red patches and purulent pustules all over the body since 3 days after taking Cefadroxil. Physical examination showed papules and pustules with erythema base. Eosinophilia was found on laboratory examination. Skin biopsy results supported the diagnosis of AGEP with hyperkeratosis, mild spongiosis, and inflammation in the dermis. Based on the history, clinical presentation, laboratory and biopsy results, the patient was diagnosed with AGEP suspected as an allergic reaction to Cefadroxil. The patient was hospitalized with systemic and supportive therapy. This case emphasizes the importance of thorough evaluation including history, clinical findings, and supporting examinations in differentiating AGEP and GPP.